The Effect of Product Placement on Brand Awareness of Cleo in Denny Sumargo's Youtube Videos Among Generation Z - Yuliawan, Muhammad Nur Fairuz; Saputro, Edy Purwo (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze how the concept of product placement in Denny Sumargo's CURHAT BANG YouTube show affects CLEO's brand awareness, considering the many competing brands of drinking water on the market and the concept of product placement applied in the YouTube show, which is done alternately with various brands in each episode aired. This research is explanatory quantitative research. The population in this study are subscribers of the YouTube account CURHAT BANG Denny Sumargo. The sampling technique used in this study is non-probability sampling with purposive sampling technique. The sample size in this study is determined using a formula developed by Slovin. The number of samples in this study was 100 respondents. Data collection in this study used questionnaires distributed through Google Forms and measured using a Likert scale. The data analysis technique in this study used the IBM SPSS Statistics application with stages of validity testing, reliability testing, normality testing, regression testing, and model feasibility testing. The results of this study indicate that product placement has a significant effect on brand awareness in the YouTube show Curhat Bang Denny Sumargo among Gen Z. Product placement carried out strategically in the show, whether through visual display, audio mention of the brand, or relevance to the storyline, can increase consumer awareness of the brand. Of the three indicators tested, visual placement proved to be the most dominant aspect in shaping audience memory and brand recognition